Natural Product Interventions for Chemotherapy and Radiotherapy-Induced Side Effects - Zhang, Qing-Yu; Wang, Fei-Xuan; Jia, Ke-Ke; Kong, Ling-Dong (Frontiers in Pharmacology, 2018)
Cancer is the second leading cause of death in the world. Chemotherapy and radiotherapy are the common cancer treatments. However, the development of adverse effects resulting from chemotherapy and radiotherapy hinders the clinical use, and negatively reduces the quality of life in cancer patients. Natural products including crude extracts, bioactive components-enriched fractions and pure compounds prepared from herbs as well as herbal formulas have been proved to prevent and treat cancer. Of significant interest, some natural products can reduce chemotherapy and radiotherapy-induced oral mucositis, gastrointestinal toxicity, hepatotoxicity, nephrotoxicity, hematopoietic system injury, cardiotoxicity and neurotoxicity. This review focuses in detail on the effectiveness of these natural products, and describes the possible mechanisms of the actions in reducing chemotherapy and radiotherapy-induced side effects. Recent advances in the efficacy of natural dietary supplements to counteract these side effects are highlighted. In addition, we draw particular attention to gut microbiotan in the context of prebiotic potential of natural products for the protection against cancer therapy-induced toxicities. We conclude that some natural products are potential therapeutic perspective for the prevention and treatment of chemotherapy and radiotherapy-induced side effects. Further studies are required to validate the efficacy of natural products in cancer patients, and elucidate potential underlying mechanisms.